El branding en el comercial “stop market” Parroquia El Salto de la ciudad de Babahoyo. - Mayorga Sánchez, Darío Ronald (2023)
Branding within the business world is the process in which the development and diffusion of a brand is followed and analyzed through the implementation of a series of processes such as analysis, strategy, design and application that involve research and communication that if handled strategically will ensure that said business That is why in the present case study, branding and its incidence within the commercial premises "Stop Market" were analyzed in a detailed way, using the inductive method as a methodology in its development, which was carried out through a series of questions addressed to the collaborators of said business, the administrative managers and the consumers.